2022
DOI: 10.1371/journal.pgen.1010168
|View full text |Cite
|
Sign up to set email alerts
|

Combined analyses of RNA-sequence and Hi-C along with GWAS loci—A novel approach to dissect keloid disorder genetic mechanism

Abstract: Keloid disorder is a tumour-like disease with invasive growth and a high recurrence rate. Genetic contribution is well expected due to the presence of autosomal dominant inheritance and various genetic mutations in keloid lesions. However, GWAS failed to reveal functional variants in exon regions but single nucleotide polymorphisms in the non-coding regions, suggesting the necessity of innovative genetic investigation. This study employed combined GWAS, RNA-sequence and Hi-C analyses to dissect keloid disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Ultimately we focused on rs12504972 whose location was intron/5′UTR region of TSPAN5 ( Table S2 ); pathogenicity was supported by DANN, GenoCanyon, ReMM and fitCons ( Table S3 ). Nowadays, Hi-C is emerging as a new strategy to dissect pathogenic mechanism of SNPs as molQTL (molecular quantitative trait locus) of which majority are noncoding regulatory genetic elements [ 29 , 30 ]. We found that rs12504972 displayed a loop with TSPAN5 in Hi-C data in KD-related cells/tissues: HUVEC and THP-1 cell line; Ventricle left and right ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately we focused on rs12504972 whose location was intron/5′UTR region of TSPAN5 ( Table S2 ); pathogenicity was supported by DANN, GenoCanyon, ReMM and fitCons ( Table S3 ). Nowadays, Hi-C is emerging as a new strategy to dissect pathogenic mechanism of SNPs as molQTL (molecular quantitative trait locus) of which majority are noncoding regulatory genetic elements [ 29 , 30 ]. We found that rs12504972 displayed a loop with TSPAN5 in Hi-C data in KD-related cells/tissues: HUVEC and THP-1 cell line; Ventricle left and right ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, excessive angiogenesis and prolonged re-epithelialization can extend the release of profibrotic growth factors. In the last few years, many biomolecules have been implicated in hypertrophic scarring; however, their exact mechanisms have yet to be fully elucidated, in part due to the complexity and overlapping nature of wound healing processes [51][52][53]. The main treatment of hypertrophic scars is prevention as possible, especially in a planned surgery.…”
Section: Hypertrophic Scarringmentioning
confidence: 99%
“…Recently, Aghmandy et al proposed that signaling in both keratinocytes and fibroblasts is disrupted in keloid pathology and that the methylation status of keloids could be implicated in the mechanisms of keloid scar formation and remission [56]. In addition, some mutations have been described in the Asian population, suggesting an individual predisposition as seen in habitual clinical practice [51].…”
Section: Keloidsmentioning
confidence: 99%
“…wound healing, and visible and elevated scars. [8][9][10] In contrast to normal skin (NS), hypertrophic scar (HS) is characterized by excessive proliferation of the dermal tissue, in a tumor-like growth mode, but HS generally did not extend the initial damage site unlike keloids. 11 The pathophysiology of hypertrophic scarring has been linked to several signaling pathways or cytokines, including epigenetic modification processes, S100A2, PI3K/Akt, TGF-β, and the SMAD pathway.…”
mentioning
confidence: 99%